Solid-State Fermentation of Aspergillus niger to Optimize Extraction Process of Isoliquiritigenin from Glycyrrhiza uralensis. (28th November 2020) - Hao, Jingwei; Li, Dianwei; Jing, Yunrong; Zhang, Lei; Liu, Jiahui; Ji, Yubin
Abstract : We successfully extracted isoliquiritigenin from Glycyrrhiza uralensis via fermentation with Aspergillus niger and ultrasonic-assisted extraction. In brief, we used A. niger fermentation to culture G. uralensis powder, and we optimized some key parameters such as reaction conditions of pH, inoculation concentration of A. niger, fermentation time, and solid-liquid ratio. Based on a single-factor experiment, we utilized the response surface methodology (RSM) approach to optimize this extraction procedure. Using the RSM approach, optimized conditions of pH = 3.694, the solid-liquid ratio = 1 : 2.155, and the inoculation concentration of A. niger = 1466745 were selected. Optimized conditions resulted in an extraction efficiency of 1.525 mg/g. These results showed that the extraction of isoliquiritigenin was most affected by pH and then the time of fermentation and the solid-liquid ratio. Overall, the developed extraction technique yielded 5 times the amount of isoliquiritigenin when compared to traditional methods.